The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0187211
|View full text |Cite
|
Sign up to set email alerts
|

Half of rifampicin-resistant Mycobacterium tuberculosis complex isolated from tuberculosis patients in Sub-Saharan Africa have concomitant resistance to pyrazinamide

Abstract: BackgroundBesides inclusion in 1st line regimens against tuberculosis (TB), pyrazinamide (PZA) is used in 2nd line anti-TB regimens, including in the short regimen for multidrug-resistant TB (MDR-TB) patients. Guidelines and expert opinions are contradictory about inclusion of PZA in case of resistance. Moreover, drug susceptibility testing (DST) for PZA is not often applied in routine testing, and the prevalence of resistance is unknown in several regions, including in most African countries.MethodsSix hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…The prevalence of pncA mutations among MDR-TB cases from 32 different countries in six WHO regions varied widely ranging from 21.4% in Yunnan Province of China12 and 39.5% in Pakistan7 to 81.3% in Belarus7 and 87.8% in Republic of Korea 38. In addition, the prevalence of pncA mutations among previously treated TB cases from six WHO regions also varied extensively ranging from 4.7% in South Africa,7 8.9% in Pakistan7 and 13.8% in Bangladesh7 to 36.2% in Zunyi, China, 66.7% in Rwanda10 and 70.8% in George 11Table 4The Prevalence Of pncA Mutations In M. tuberculosis Isolates From Six Different WHO Regions And 32 Countries Of The WorldPrevalence Of pncA Gene Mutations, % (Number Of TB Isolates Tested)WHO RegionsMDR/RR CasesNew CasesPT CasesTotal CasesAfrica Burundi965.7% (35)N/AN/AN/A Sub-Sahara Africa (12 countries)1054.3% (573)63.9% (72)49.0% (453)51.0% (525) Cameroon1049.6% (133)55.6% (9)50% (116)50.4% (125) CAR1028.6% (35)N/A23.3% (30)N/A DRC1073.7% (95)75% (16)68.7% (67)69.9% (83) Niger1039.6% (48)N/A39.1% (46)N/A Rwanda1067.3% (101)69.0% (42)66.7% (36)67.9% (78) Senegal1033.3% (39)N/A31.4% (35)N/A…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of pncA mutations among MDR-TB cases from 32 different countries in six WHO regions varied widely ranging from 21.4% in Yunnan Province of China12 and 39.5% in Pakistan7 to 81.3% in Belarus7 and 87.8% in Republic of Korea 38. In addition, the prevalence of pncA mutations among previously treated TB cases from six WHO regions also varied extensively ranging from 4.7% in South Africa,7 8.9% in Pakistan7 and 13.8% in Bangladesh7 to 36.2% in Zunyi, China, 66.7% in Rwanda10 and 70.8% in George 11Table 4The Prevalence Of pncA Mutations In M. tuberculosis Isolates From Six Different WHO Regions And 32 Countries Of The WorldPrevalence Of pncA Gene Mutations, % (Number Of TB Isolates Tested)WHO RegionsMDR/RR CasesNew CasesPT CasesTotal CasesAfrica Burundi965.7% (35)N/AN/AN/A Sub-Sahara Africa (12 countries)1054.3% (573)63.9% (72)49.0% (453)51.0% (525) Cameroon1049.6% (133)55.6% (9)50% (116)50.4% (125) CAR1028.6% (35)N/A23.3% (30)N/A DRC1073.7% (95)75% (16)68.7% (67)69.9% (83) Niger1039.6% (48)N/A39.1% (46)N/A Rwanda1067.3% (101)69.0% (42)66.7% (36)67.9% (78) Senegal1033.3% (39)N/A31.4% (35)N/A…”
Section: Discussionmentioning
confidence: 99%
“…bovis , which is intrinsically PZA resistant due to a lineage wide pncA mutation, L6 is susceptible to PZA. However, L6 grows slower in vitro and is less dependent on aerobic metabolism[28], both of which may increase its tolerance to certain TB drugs like isoniazid that mainly target rapidly dividing bacteria [3,29]. In support of the slower response to TB treatment of L6, a study in The Gambia showed slower immunological recovery of patients treated for L6 relative to L4 [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, it seemed to have limitations in settings where a "mixture" of MDR strains was present, for instance where there was additional resistance, especially to pyrazinamide, or where it is difficult to obtain a complete resistance profile of isolated strains [16][17][18][19]. Pyrazinamide resistance, however, can often be associated with rifampicin resistance [20].…”
Section: Dots-plusmentioning
confidence: 99%
“…The potential wide use of the regimen will, as for BPaL, be conditional to minimisation of creation of resistance to its new components. Concerningly, the presence of resistance to the fluoroquinolones and pyrazinamide among rifampicin-resistant cases, although frequently low, is already well documented in certain settings [20,21,37].…”
Section: While This Historical Account Summarises the Past And Presenmentioning
confidence: 99%